2013
DOI: 10.1071/nb12116
|View full text |Cite
|
Sign up to set email alerts
|

Are pregnancy outcomes associated with risk factor reporting in routinely collected perinatal data?

Abstract: Aim:To assess reporting characteristics of commonly dichotomised pregnancy outcomes (e.g. preterm/term birth); and to investigate whether behaviours (e.g. smoking), medical conditions (e.g. diabetes) or interventions (e.g. induction) were reported differently by pregnancy outcomes. Methods: Further analysis of a previous validation study was undertaken, in which 1680 perinatal records were compared with data extracted from medical records. Continuous and polytomous variables were dichotomised, and risk factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…A 1998 validation study showed high levels of accuracy and reliability compared with medical records for dichotomised perinatal variables such as preterm birth, low and high birthweight, Apgar scores, perineal trauma, regional analgesia and stillbirth (Kappa 0.95-1.00, sensitivities 94.7-100.0%). 11 The lower estimate of HBV prevalence from the PDC compared with prevalence using linked NCIMS records is consistent with previous analyses of PDC data for rarer events. 12 The level of agreement was similar for private and public hospitals, in contrast to a study of PDC versus hospital records of postpartum haemorrhage requiring transfusion, which found poorer agreement for private hospitals.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A 1998 validation study showed high levels of accuracy and reliability compared with medical records for dichotomised perinatal variables such as preterm birth, low and high birthweight, Apgar scores, perineal trauma, regional analgesia and stillbirth (Kappa 0.95-1.00, sensitivities 94.7-100.0%). 11 The lower estimate of HBV prevalence from the PDC compared with prevalence using linked NCIMS records is consistent with previous analyses of PDC data for rarer events. 12 The level of agreement was similar for private and public hospitals, in contrast to a study of PDC versus hospital records of postpartum haemorrhage requiring transfusion, which found poorer agreement for private hospitals.…”
Section: Discussionsupporting
confidence: 75%
“…However, we hypothesise that, as the data collection practice becomes more ingrained in the health system, sensitivity will improve, as it did for the perineal trauma 12 and postpartum haemorrhage data 13 , and to the level of accuracy and reliability of other dichotomised variables suggested by previous validation studies. 11 If reporting of maternal HBV status in the PDC data becomes more reliable, it could be used to determine HBV prevalence across different AHSs and population groups, as well as to monitor prevalence changes over time, as has been done in previous studies using linked data. 6,7 Variations in accuracy across AHSs, and important sociodemographic factors such as country of birth also require further analysis over time to determine if there are consistent factors that affect the accuracy of reporting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to completeness, the information is available and easily obtainable. Accuracy and concordance of pregnancy outcomes (including birth weight, gestational age, and Apgar score of dichotomized medical record data) are generally considered as good and unbiased 1 . Brazilian studies have shown that birth weight 21 and fifth-minute Apgar score showed good to excellent reliability 5 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study highlights that, if improved detection is responsible for the apparent increase in OASIS incidence, such detection is not occurring among vacuum deliveries because there was no evidence of an increasing trend in this group. Whether differential reporting has occurred, with higher rates of third‐ and fourth‐degree tears being reported among groups with known risk factors (such as instrumental deliveries), is also not known; however, a local validation study provides some reassurance that this is not the case [25]. Comparisons of sensitivities and PPVs for perineal trauma between non‐instrumental and instrumental deliveries were reported as not being statistically different (sensitivity 96.6 vs 97.9, PPV 96.0 vs 98.6, respectively) in the validation study [25].…”
Section: Discussionmentioning
confidence: 99%